Integration of palliative care in African health systems: a systematic review - Court, Lara A (Department of Public Health and Family Medicine, 2019)
Millions of people need palliative care worldwide for symptoms associated with life-threatening illnesses, yet few receive it. This is particularly true in low-and-middle income countries, meaning that most are left without support and pain relief at the end of their life. Access to palliative care is now being understood as a human right and the ethical responsibility of health systems. This has resulted in increased international focus and a call to integrate palliative care into health systems to promote access, and inversely to strengthen health systems. Yet how to do this in low-and-middle income countries is unclear. This study used scoping and systematic review methods to provide synthesised evidence on the approaches and interventions being used to integrate palliative care into African health systems, as well as describe lessons that can be learnt from these efforts. 40 articles were identified in the systematic review that described 51 different interventions that integrated palliative care into part of the health system in one or more African countries. The integration of palliative care services was rarely linked to health systems strengthening and concepts associated with integration were used inconsistently, if used at all. Core themes emerged on facilitators and barriers to the integration of palliative care into health systems. Facilitators included the use of a system-wide approach, the creation of sustainable partnerships, and making the patient central to integration interventions. The health system also needs to be able to support integration. This requires the presence of necessary policies and resources for palliative care, together with sufficient health workers who are trained and motivated to provide palliative care. Findings provide contextual evidence to guide implementors and decision makers seeking to integrate palliative care into health systems in Africa, as well as other low and-middle income countries.